AUDIT TENURE, AUDIT LAG, OPINION SHOPPING, LIQUIDITY AND LEVERAGE, THE GOING CONCERN AUDIT OPINION - Lisa Theresia; Temy Setiawan (SEAN Institute, 2023)
Going concern audit opinion is an opinion given by the auditor to a company whose ability to maintain its business continuity is doubtful. This research was conducted with the aim to determine the effect of Audit Tenure, Audit Lag, Opinion Shopping, Liquidity & Leverage Ratio on Going Concern Audit Opinions. This research is done using the quantitative method research with secondary data obtained from the financial reports and audit reports included in the annual reports of manufacturing companies listed on the IDX for 2018-2021. The sample of this study were 102 manufacturing companies which were carried out using the purposive sampling method and processed with IBM SPSS version 25. In this study the results obtained were that the liquidity ratio did not affect the Going Concern Audit Opinion. Meanwhile, Audit Tenure, Audit Lag, Opinion Shopping and Leverage Ratio affect the going concern audit opinion.